PENGARUH PERILAKU TIDAK JUJUR DAN KOMPETENSI MORAL TERHADAP KECURANGAN AKADEMIK (ACADEMIC FRAUD) MAHASISWA AKUNTANSI - Dyon Santoso; Harti Budi Yanti (Media Riset Akuntansi, Auditing & Informasi, 2015)
The objectives of this research is to analyze and provide empirical proves about the influences of dishonesty behavior dan moral competence towards academic fraud of accounting students. The variable used in the research are dishonesty behavior and moral competence. The population of the research is the accounting students from Trisakti University, Bina Nusantara University, and Indonesia Banking School. 242 respondents has been involved as sampels in the research.Data used in the research consist of primary data collected using a questionaire.  Multiple regression analysis will be used in the data analysis to test the hypotheses, and the data will be tested using the 20 version of SPSS The result of the test shows us that dishonesty behavior is proven to have an effect on the academic fraud of accounting students. While moral competence has not shown an effect on the academic fraud of accounting students.Key words : Dishonesty Behavior, Moral Competence, Academic Fraud